A new species of Dienerella Reitter, 1911 from Kazakhstan, with an updated checklist of Dienerella species and summary of their distribution (Coleoptera: Latridiidae: Latridiinae) - Plewa, Radosław; Rücker, Wolfgang H. (Zootaxa, 2020)
Dienerella (Dienerella) katarzynae sp. nov. from Kazakhstan is described. The generic characteristics and diagnostics, including the aedeagus, are illustrated. A key to the subgenus Dienerella, a group of similar species including D. beloni, D. pilifera and D. elegans, is given, and an updated global checklist of Dienerella species is provided. To date, 41 taxa in the genus Dienerella (19 species in the subgenus Cartoderema and 22 species in the subgenus Dienerella) have been described globally. In this paper, we summarize the distribution and endemism of Dienerella species worldwide: currently, 15 endemic species from the genus Dienerella (5 species in the subgenus Cartoderema and 10 species in the subgenus Dienerella) are known.